Performance analysis on direct torque controlled induction motor drive with varying hysteresis controller bandwidth - S. Allirani; N. Subha Lakshmi; H. Vidhya (Institute of Advanced Engineering and Science, 2020)
The fore most issue in DTC based induction motor drive is its torque ripples. The core objective of this paper is to reduce the electromagnetic torque ripples by varying the hysteresis controller bandwidth. Space Vector Modulation (SVM) based Direct Torque Controlled (DTC) induction motor drive is simulated in MATLAB/SIMULINK environment and its performance is studied with step change in load torque. The influence of hysteresis controller bandwidth on the performance of induction motor drive is analysed in terms of stator flux and electromagnetic torque ripples. The electromagnetic torque response and the stator flux trajectory for different values of hysteresis controller bandwidth are obtained and the results are presented.